First experimental evidence of non-collinear spin structure in CaCu2.3Ti3.3Fe1.4O12 quadruple perovskite through low-temperature, in-field 57Fe Mossbauer spectroscopy. Issue 8 (1st June 2020) - Pansara, Pooja R.; Raval, Pooja Y.; Pandit, Rabia; Nehra, Jagdish; Dolia, Satya N.; Modi, Kunal B.
Abstract: A polycrystalline sample of quadruple perovskite oxide, CaCu2.3 Ti3.3 Fe1.4 O12, was synthesized and characterized by zero-field and in-field ( H̄ app = 50 kOe) 57 Fe Mossbauer spectroscopy at 5 K. The presence of ΔmI = 0 spectral lines in Mossbauer spectrum recorded with H̄ app parallel to the direction of γ-ray transmission provides unambiguous affirmation for the presence of canting angles among individual moments and the direction of net-sublattice magnetization. The observed non-collinear spin structure is well supported by the M(H) loop characteristic. The canting angle, θc = 67.8°, determined from Mossbauer spectral analysis is in accordance with the canting angle, θM = 71.2°, calculated from the site magnetic moments. This led to cluster-spin-glass like magnetic ordering well reflected in the M(T) curve. The effects of low-temperature and applied magnetic field on the line shape of the Mossbauer spectra and nuclear hyperfine interaction parameters have also been discussed in detail.